2017
DOI: 10.1111/ceo.12890
|View full text |Cite
|
Sign up to set email alerts
|

Self‐care tools to treat depressive symptoms in patients with age‐related eye disease: a randomized controlled clinical trial

Abstract: Self-care tools plus telephone coaching led to a modest improvement in depressive symptoms in patients with age-related eye disease. Additional research on how to maximize their effect is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…153 Self-guided CBT has also led to a significantly greater reduction in depressive symptoms among patients with AMD relative to usual care, although improvements in other outcomes, including anxiety and self-efficacy, were not observed. 154 Cognitive and behavioral approaches have also been tested in other visually impaired populations, such as people with blindness. In one study, individuals with blindness receiving Rational Emotive Behavior Therapy (REBT), a type of cognitive therapy, reported significant reductions in irrational beliefs, depression, anxiety, and stress and improvements in self-esteem, while these same changes were not observed in the control group.…”
Section: Cognitive Behavioral Interventionsmentioning
confidence: 99%
“…153 Self-guided CBT has also led to a significantly greater reduction in depressive symptoms among patients with AMD relative to usual care, although improvements in other outcomes, including anxiety and self-efficacy, were not observed. 154 Cognitive and behavioral approaches have also been tested in other visually impaired populations, such as people with blindness. In one study, individuals with blindness receiving Rational Emotive Behavior Therapy (REBT), a type of cognitive therapy, reported significant reductions in irrational beliefs, depression, anxiety, and stress and improvements in self-esteem, while these same changes were not observed in the control group.…”
Section: Cognitive Behavioral Interventionsmentioning
confidence: 99%
“…The studies included in this review examined the effectiveness of psychosocial and psychological interventions which were mainly composed of cognitive-behavioural techniques such as self-management, self-help, problem solving, behavioural activation, and emotion-focused intervention. Although all studies have tested the effectiveness of the intervention programme to reduce symptoms of depression, only four studies included anxiety as an outcome measure (59)(60)(61)(62). Five out of seven RCT studies suggested effective interventions to prevent and treat depression in AMD patients (53,55,57,59,61), and one of these studies also showed positive outcomes for anxiety (61).…”
Section: Discussionmentioning
confidence: 99%
“…Although all studies have tested the effectiveness of the intervention programme to reduce symptoms of depression, only four studies included anxiety as an outcome measure (59)(60)(61)(62). Five out of seven RCT studies suggested effective interventions to prevent and treat depression in AMD patients (53,55,57,59,61), and one of these studies also showed positive outcomes for anxiety (61). However, only 4 studies in our review had included an outcome measure for anxiety (60)(61)(62)(63), which suggests the need for additional research investigating the effect of psychological and psychosocial interventions on anxiety related to AMD.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to decrease depressive symptoms include greater screening and targeted interventions in high-risk groups. 44,45 Aging (CLSA) is provided by the Government of Canada through the Canadian Institutes of Health Research (CIHR) under grant reference: LSA 94473 and the Canada Foundation for Innovation. This research has been conducted using the CLSA dataset, Baseline Comprehensive Dataset…”
Section: Crosssectionalmentioning
confidence: 99%